Implementasi Kebijakan Anti Perundungan Untuk Meningkatkan Kenyamanan Belajar Peserta Didik Di Madrasah Ibtidaiyah At-Taqwa Arcamanik Bandung - Riska Marfita (Edukasiana: Journal of Islamic Education, 2024)
Abstract The purpose of this research is to reveal that anti-bullying policies in schools are very important to implement because they can help reduce the lack of bullying among students. The method used in this research is qualitative with a case study approach. The place of this research is Mi At-Taqwa Arcamanik Bandung. The main data sources are the student affairs coordinator, extracurricular coordinator, women's coordinator, teachers and three Mi At-Taqwa Arcamanik Bandung students. Secondary sources are books, journals and articles. And documentary sources are in the form of observations and documentation in the form of photographs. Data collection techniques include observation, interviews and documentation. And inductive data analysis techniques using the Miles and Huberman model. The results of this research show that the Mi At-Taqwa Arcamanik Bandung school, in anticipating bullying, made a number of anti-bullying policies, including: (1). Identify bullying which has 4 aspects, including: (a). forms of bullying, (b). identification of the perpetrator/victim of bullying, (c). identification of the bad impacts of bullying, (d). create discipline and sanctions. And (2). Collaborate with related parties. Keywords: Implementation, Anti-Bullying, School Policy.